A NEW DEVICE TO PROTECT HONEY BEES FROM THE PREDATORY WASPS AT THE HIVE ENTRANCE OF APIS MELLIFERA L. COLONIES - SRIVASTAVA, S.; KUMAR, ARUN; KASHYAP, N.P.; CHANDEL, Y.S.; RAJ, DESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Predatory behaviour of Vespa viz. V. mandarinia Smith, V. velutina auraria Smith, V. tropica (Leefrnansi) Vecht, V. basalis Smith and V orientalis Linnaeus on the hive entrance of A. mellifera L. is described. V. mandarinia and V. velutina auraria causing serious damages to A. mellifera colonies took3.9±1.2 and 21.2 ±15.3 seconds to catchabee, respectively. The developed new device, 'Bee-Wasp Protector effectively protected bees from wasps' attack at the hive entrance.